Feeling the Heat: Temperature, Physiology & the Wealth of Nations - Geoffrey Heal; Jisung Park (Center for Economic Studies and ifo Institute (CESifo), 2014)
Does temperature affect economic performance? Has temperature always affected social welfare through its impact on physical and cognitive function? While many studies have explored the indirect links between climate and welfare (e.g. agricultural yield, violent conflict, or sea-level rise), few address the possibility of direct impacts operating through human physiology. This paper presents a model of labor supply under thermal stress, building on a longstanding physiological literature linking thermal stress to health and task performance. A key prediction is that effective labor supply - defined as a composite of labor hours, task performance, and effort - is decreasing in temperature deviations from the biological optimum. We use country-level panel data on population-weighted average temperature and income (1950-2005), to illustrate the potential magnitude of the effect. Using a fixed effects estimation strategy, we find that hotter-than-average years are associated with lower output per capita for already hot countries and higher output per capita for cold countries: approximately 3%-4% in both directions. We then use household data on air conditioning and heating expenditures from the US to provide further evidence in support of a physiologically based causal mechanism. This more direct causal link between climate and social welfare has important implications for both the economics of climate change and comparative development.
Keywords: Q54; 330; labor productivity; climate change; development; economic geography; health and human capital; economic growth